One-Step Electrodeposition of Chiral Plasmonic Gold Nanostructures for Enantioselective Sensing - Igseon GU; Takuya ISHIDA; Tetsu TATSUMA (Electrochemistry, 2022)
Chiral plasmonic nanostructures attract much attention because of their potential applications to advanced optical materials and enantioselective sensors. However, the latter has been fabricated on the basis of top-down methods, which take time and cost. Here we developed a one-step method for preparation of chiral gold nanostructures immobilized on an electrode by a simple electrodeposition in the presence of L- or D-cysteine. Opposite circular dichroism (CD) spectra were obtained by using L- or D-cysteine, while achiral structures were deposited for racemic cysteine or in the absence of cysteine. The chirality was attributed to geometries of the nanostructures. Chiral gold nanostructures electrodeposited in the presence of L-cysteine gave higher CD signals to (S)-enantiomer than those to (R)-enantiomer of 1,2-propanediol, and vice versa. TiO2-coated electrodes were also used as a substrate for the electrodeposition of chiral nanostructures, so that the chiral plasmonic electrodes would be employed for optoelectronic and photoelectrochemical applications.